Pertumbuhan Bibit Meranti Tembaga (Shorea leprosula) Umur 6 BulandariTiga Populasidi Kalimantan Timur - Mashudi Mashudi; Mudji Susanto; Sugeng Pudjiono (Universitas Sebelas Maret, 2018)
Shorea leprosula Miq. is a member of the Dipterocarpaceae which has a high genetic diversity. In Indonesia, this species is naturally spread on the islands of Sumatra, Kalimantan and Maluku. The purpose of this paper is to investigate the diversity of S. leprosula seedlings at 6 months of age from three populations in East Kalimantan. The experimental design used was Complete Randomized Design (CRD) with 10 seeds for each mother tree from three populations (Muara Wahau 15 mother trees, Berau 12 mother trees and Kenangan 20 mother trees).In this study the mother tree is nested in the population. The result of variance analysis showed that the population sources and mother tree had significant effect on high growth, stem diameter and the index of robustness of S. leprosula seedlings at 6 months of age. Kenangan population and Muara Wahau population are the best population in high growth and stem diameter, while the best robustness index is occupied by Berau population. The mother trees were separated in 19 groups of differences on high growth characters, 15 groups of differences in stem diameter growth characters and 12 groups of differences in robustness index characters. The best high growth is occupied by 4 mother trees with a range of 57.00 - 62.64 cm, the best stem diameter is occupied by 5 mother trees with a range of 4.76 - 5.47 mm and the best robustness index is occupied by 14 mother trees with values range 7.66 - 10.12.